Portaria PGR/MPF nº 887, de 27 de outubro de 2022 - Antonio Augusto Brandao de Aras (DOU, Brasília, DF, 7 nov. 2022. Seção 2, p. 61., 2022)
Altera a Portaria PGR/MPF nº 758, de 19 de setembro de 2022.